Technology and disaster management in Nigeria: prospects and challenges (2020)
The use of technology in disaster management is not a new phenomenon globally, but in Nigeria such technology has not been put to effective use by disaster management agencies. This paper reviews the present state of technology usage in disaster management in Nigeria with, the aim of recommending prospective interventions in the future. Extant literature was used in analysing the prospects and challenges of deploying technology during disaster management process. This paper thus examines the centrality of technology to disaster management in Nigeria, identifies new and not-so-new technology that could be useful in handling disaster issues, and highlights the important elements of some of the identified technology, their strengths as well as their limitations. Evident prospects and challenges facing the implementation of technology in disaster management in Nigeria are discussed. The paper makes recommendations toward a more technology-savvy disaster management system for the country through adequate training of disaster management officials, provisions of equipment and capacity building efforts to enhance synergy between private and public sectors.